Evaluation of Soft Skill Training to Strengthen Collaborative Management of National Parks in Sumatera, Indonesia - Thomas Oni Veriasa; Muchamad Muchtar; Evi Indraswati; Ajeng Miranti Putri (Jurnal Manajemen Hutan Tropika, 2021)
A series of soft skill training in four national parks of Sumatra Island were conducted by PILI Green Network NGO, DG of Natural Resources and Essential Ecosystem Conservation of the MoEF, and Sumatran Tiger Project-UNDP for 12 months in 2019. The training aims at improving soft skill capacity of the national park staff on conflict management and collaborative actions with the communities in the buffer zone. This paper aims 1) to evaluate the soft skill training programme achievement by employing Kirkpatrick’s evaluation model; 2) to analyse factors of Training Program participants that influence on the individual soft skill enhancement by using multiple linear regression analysis. The results show that soft skill training was effective to increase the knowledge and skill of the participating staff, especially in participatory approaches, conflict management, and the development of a collaborative business model. Three factors, including work experience, the suitability of background education and similar training experience, have significant influences on the individual soft skill enhancement. Training design, which was bottom-up and participatory based on the needs of the resorts as a spearheading of national park management, contributes to the success of the training implementation. The training has created a ‘common room’ for the participating staff and the communities in terms of opening communication and development of collaborative action plans at each national park.